Sensitive elements based on bacteriorhodopsin for fiber-optics sensors of chemical components - Sharkany, Y. P.; Trikur, I. I.; Korposh, Serhiy A.; Ramsden, Jeremy J. (Cranfield University, 2005)
The sensitive thin film elements based on bacteriorhodopsin in polymeric matrixes for the multichannel fiber-optical sensor system of measurement of chemical composition of gas mixtures are offered. It is shown, that modification of films compositions by the photosensitizing chemical additives changes the photocycle parameters and exhibits selectivity to the effect of various gases.